المقاومات الشعبية للاستعمار الفرنسي بناحية عنابة 1832م -1852م - بورمضان, عبد القادر; بورغدة, رمضان (My University, 2022)
لقد شكل احتلال مدينة عنابة في ربيع 1832م من طرف الفرنسيين بداية لسلسلة من المقاومات الشعبية المسلحة امتدت بين 1832م ـ1852م .قادها بعض الشيوخ والزعماء تارة بالتحالف مع احمد باي واحيانا اعتمادا على دعم القبائل ، حاولت هده المقاومات التعطيل والحد من التوسع الفرنسي ،ما دفع بالسلطات الفرنسية انتهاج اساليب قمعية لمواجهة خطر هده المقاومات التى رغم تعددها لم تنجح في تحقيق هدفها لعدة اسباب ابرزها نقص التنظيم ،وانعدام التنسيق ما سهل اخمادها . It formed the occupation of the city of annaba in the spring of 1832 by the french the beginning of a series of popular resistance that extended between 1832-1852 led by same "sheikhs"and "leader",sametimes in alliance with "Ahmed BEY"and depending cern the support of the tribes. This resistance ,tried to disrupt and limit the French expansion ,prompting the French authorities to adopt repressive methods to confort the donger of these resistance,which despite their diversity ,did not succeeding achieving theire gool forseveral reasons ,most the lack of organization and lack of coordination,which made it easier to put them down.
مقال
Keywords: المقاومة,الغارات,الأرض المحروقة,القبائل’الحملات; Resistance ,Raids,Scorched earth ,Tribes ,campaigns